2020
DOI: 10.1115/1.4048142
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Flow Rate Fluctuations in Single- and Two-Blade Pumps

Abstract: A comparative study on the highly unsteady flow field in single- and two-blade pumps is performed. Stationary pump characteristics, as well as pressure and flow rate fluctuations, are presented. Wall pressure fluctuations are measured in the suction and pressure pipe as well as at several locations within the volute casing by piezoresistive transducers. Flow rate fluctuations are evaluated by a recently presented measurement system based on an electromagnetic flow meter [1]. Measurements are accompanied by 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…As a result, scholars have conducted a great deal of research on the flow field characteristics of impeller blades. Persch et al [5] studied and researched the highly unstable flow field characteristics in single-vane and two-vane pumps by supplementing the measured and simulated results to compare the pressure and flow undulation characteristics of the two pump types. Ju et al [6] conducted a comparative analysis of different shapes of vanes from the internal vortex structure and found that 2D and 3D forward-angle vanes have a better effect on pump hydraulic performance than conventional radial straight vanes, producing more intense fore-and-aft swirls and smaller axial and radial eddy currents in the vane channel and higher pump efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, scholars have conducted a great deal of research on the flow field characteristics of impeller blades. Persch et al [5] studied and researched the highly unstable flow field characteristics in single-vane and two-vane pumps by supplementing the measured and simulated results to compare the pressure and flow undulation characteristics of the two pump types. Ju et al [6] conducted a comparative analysis of different shapes of vanes from the internal vortex structure and found that 2D and 3D forward-angle vanes have a better effect on pump hydraulic performance than conventional radial straight vanes, producing more intense fore-and-aft swirls and smaller axial and radial eddy currents in the vane channel and higher pump efficiency.…”
Section: Introductionmentioning
confidence: 99%